Targeting Value-Driven Quality Improvement for Laparoscopic Cholecystectomy in Michigan. Issue 1 (January 2019) - Sheetz, Kyle H.; Kenney, Brooke; Dupree, James M.; Campbell, Darrell A.; Englesbe, Michael J.
Abstract : Objective: The purpose of this study was to evaluate complete episode expenditures for laparoscopic cholecystectomy, a common and lower-risk operation, to characterize novel targets for value-based quality improvement. Summary Background Data: Despite enthusiasm for improving the overall value of surgical care, most efforts have focused on high-risk inpatient surgery. Methods: We identified 19, 213 patients undergoing elective laparoscopic cholecystectomy from 2012 to 2015 using data from Medicare and a large private payer. We calculated price-standardized payments for the entire surgical episode of care and stratified patients by surgeon. We used linear regression to risk- and reliability-adjusted expenditures for patient characteristics, diagnoses, and the use of additional procedures. Results: Fully adjusted total episode costs varied 2.4-fold across surgeons (7922–17, 500). After grouping surgeons by adjusted total episode payments, each component of the total episode was more expensive for patients treated by the most expensive versus the least expensive quartile of surgeons. For example, payments for physician services were higher for the most expensive surgeons [1932, 95% confidence interval (CI) 1844–2021] compared to least expensive surgeons (1592, 95% CI 1450–1701, P < 0.01). Overall differences were driven by higher rates of complications (10% vs. 5%) and readmissions (14% vs. 8%), and lower rates of ambulatory procedures (77% vs. 56%) for surgeons with the highest versus lowest expenditures. Projections showed that a 10% increase ambulatory operations would yield 3.6 million in annual savings for beneficiaries. Conclusions: Episode payments for laparoscopic cholecystectomy vary widely across surgeons. Although improvements in several domains would reduce expenditures, efforts to expand ambulatory surgical practices may result in the largest savings to beneficiaries in Michigan.